Formulasi dan Uji Mutu Fisik Sediaan Sabun Padat Ekstrak Biji Alpukat (Persea americana): Formulation and Physical Quality Test of Solid Soap Extract of Avocado Seeds - Sintya Zagita; Elly Purwati; Cikra Ikhda Nur Hamidah Safitri (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Research on avocado seed extract (Persea americana.) At 1% and 3% concentrations for the manufacture of solid soap preparations and physical quality testing of solid soap preparations has been carried out. Avocado seeds have the ability as an antioxidant which can inhibit the main factor in the aging process. This study aims to determine that avocado seed extract (Persea americana.) Can be used as a solid soap with a concentration of 1% and 3% which meet the physical quality test requirements which include pH test, foam power test, organoleptic test, and homogeneity test. The design of this research is experimental research. Avocado seed extract was obtained from the maceration process with 70% ethanol and phytochemical screening was carried out. Making soap formulation is done by calculating using the Lye Calculator and making soap using the Cold Process method. The research results were processed using descriptive analysis. The treatments in this research were the concentration methods added were 1% and 3%. The homogeneity test showed that the three solid soap formulations of avocado seed extract (Persea americana.) Were still homogeneous as indicated by the absence of coarse grains or particles on the surface of the avocado seed extract (Persea americana.) Solid soap which was seen in plain view on the solid soap without the addition of the extract and the concentration of 3%. Meanwhile, the concentration of 1% looks like it is semi-homogeneous. The organoleptic results showed different forms, the formula without the addition of extract and a concentration of 1% had a solid form while the formula with a concentration of 3% had a solid and hard form. The formula without the addition of the extract and the concentration of 1% has a distinctive aroma of lux soap while the formula with a concentration of 3% has a distinctive aroma of avocado seed leaves which is more concentrated, the color of the preparation in each formula is different, influenced by variations in the concentration of mango leaf extract. The high stability of the foam with a height of 9cm and a pH value is in accordance with SNI 06 - 3532 - 2016 with a pH value of 9-11.